Estrategias feministas de deconstrucción del objeto de estudio de la economía - Pérez Orozco, Amaia (Foro Interno, 2004)
This text discusses different approaches to Feminist Economics according to their proposals to redefine the object of study of economics. These proposals can be under stood as attempts to deconstruct key androcentric dichotomies such as the 87 Estrategias feministas de deconstrucción del objeto de estudio de la economía Amaia Pérez Orozco economic/non-economic and work/non-work polarities. Two main deconstruction strategies are identified, with different theoretical, empirical and political implica tions. The first one is aimed at recovering and revaluing the "other" in economic dis course, that is, domestic labour. The second one looks for a displacement of the bina ry structure through the creation of a third term or "hinge word". The concept of sus tainability of life would be the "hinge term" that allows for a revision of related con cepts such as work. Finally, this article argues that a theoretical shift of attention towards sustainability of life is occurring within Feminist Economics.